Mother’s Voice: Storytelling Approach As Postpartum Psychosocial Therapy - Ekasari, Rizqiana Dita; Satiti, Ika Arum Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effectiveness of the storytelling approach as a psychosocial therapy on postpartum maternal depression and anxiety levels. The method used is quasi-experimental design with one pretest-posttest control group design with 60 respondent. The results of the study show that before the intervention, based on the EPDS the highest score was 19 (moderate-high depression risk category) and after the intervention the highest score decreased to 13 (mild category). Meanwhile, for anxiety before the intervention, based on the STAI, the highest score was 67 (high anxiety category) and after the intervention the highest score reduced to 54 (approaching the moderate category). The results showed a significant decrease in depression scores (p < 0.05) and anxiety (p < 0.05) in the intervention group compared to the control group. In conclusion, storytelling is effective as a psychosocial therapy in reducing symptoms of depression and anxiety in postpartum mothers. Keywords: Postpartum, Psychosocial Therapy, Storytelling, Maternal Mental Health